Aspek Ekonomi Pemeliharaan Ternak Sapi Program CSR (Cooperate Social Respontibility) dalam Pola Usaha Tani Petani Kelapa Sawit di Kabupaten Tanjung Jabung Timur - Darmawi, Darlim (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The aim of this project was to reveal economical aspect of rearing beef in integrited farming system systyem in east Tanjung Jabung Regency. Method used was survey method. Including palm oil farmer reored beef catle in programe of CSR of Petrochina. Sampling is this study were farmer chosed inpurposive sampling. Statistical analysis used analisys of farm net cash flow (Soekartawi, 1995). Result of this study showed the farmer income in this method (integriled beef and falm oil was tolaly Rp. 213.053,560/year with Rp. 144,446,560/year and Rp. 68,607,000/year for beef and palm oil respectively.If might be concluded that the CSR programe bald provide the average income was Rp. 8,024,809/year/head or contributing 67,79% of total farmer income, but rearing beef cattle could beÂ  part ot farmer (farm).